Influence of internal variability on future changes in surface wind speed in China with two large ensemble simulations - Ling Yu; Hong Cao; Liang Yue (PLoS ONE, 2025)
Wind energy, as one of the renewable energy sources, plays a crucial role in the global energy system’s transition to clean energy. China possesses vast and widely distributed wind energy resources, and in recent years, it has rapidly developed and begun large-scale commercial utilization. Therefore, studying changes in surface wind speeds (SWSs) is highly important for wind energy development in China. This study utilizes two initial condition large ensemble simulations to project future changes in SWSs over China. The two sets of initial large ensemble models used are CanESM2-LE and CESM1-LE. By comparing the results from these two large ensemble models, the influence of internal variability of the climate system on SWSs in China are studied. Both models can effectively reproduce the climatological spatial distribution of SWSs in reanalysis. Results from both models indicate that external forcing leads to an increase in winter SWSs in eastern China, while SWSs decreases in the southeastern coastal areas and southwestern Tibet. In summer, SWSs exhibits a pattern of decrease in the north and increase in the south. The magnitude of wind speed changes is greater in winter than in summer. Additionally, as the projected period extends, the magnitude of these changes intensifies. The research results can provide a scientific basis for the future planning of wind power deployment.